Isolated idiopathic hypoparathyroidism that developed in adulthood: a case report - G. E. Runova; A. V. Oderiy; I. V. Glinkina; Yu. P. Sych; S. E. Moshenina; V. V. Fadeev (Сеченовский вестник)
Hypoparathyroidism is a rare endocrine disease. In most cases in adult patients, the cause of hypoparathyroidism is damage or removal of parathyroid glands during surgical interventions on the neck; other causes are rarely observed.Case report. A 52-year-old man with episodes of seizures, intense muscle pain, progressing for 7 years and resistance to treatment with myorelaxant, anxiolytics and nonsteroidal anti-inflammatory drugs was examined and hypocalcemia associated with low parathyroid hormone and excessive urinary calcium excretion was found. Ultrasound examination didn't reveal any changes in parathyroid glands. The patient was diagnosed with idiopathic hypoparathyroidism. Treatment with calcium supplements and active metabolites of vitamin D led to an improvement in clinical symptoms and laboratory parameters.Discussion. Hypoparathyroidism as part of several genetic syndromes was excluded due to the late- onset of the disease and the absence of concomitant diseases. Ultrasound of the parathyroid glands made it possible to rule out metastasis and storage diseases. It is recommended to perform genetic testing of the chromosomes 22 and 10 to exclude rare variants of syndromic hypoparathyroidism with the late-onset in the form of isolated hypocalcemia.